An empirical analysis of knowledge management’s role towards achieving projects success in the Malaysian government agencies - Sabaghpour Azarian, Mahdieh; Ahmad Dahlan, Abdul Rahman (2014)
As knowledge has been recognized as an inseparable imperative strategy of organization, organizations look at knowledge as a power which drives advantages to them. However, many organizations believe it is not about just the existence of knowledge but the organizational growth has been driven from the act of knowledge sharing. Through many established surveys, it is believed those organizations in which their management and staff practicing Knowledge Management (KM) and knowledge sharing, will grow stronger and turn to be more competitive compared to those organizations which do not or lack of KM practices. As a modern economy takes knowledge as a point to achieve project success, utilization of information and data coupled with the harnessing of people’s skills and ideas as well as their commitments and motivations. Therefore, it is undeniable that today knowledge is an essential asset of every single organization and it has become more strategic than land, labor or capital in today’s economy. This paper investigates on the importance of KM in generating projects success by analyzing the Malaysian government agencies context. In this regard, a research has been conducted amongst fifteen Malaysian government agencies to find how effective project managers integrate KM criteria and factors in order to achieve project success, indicated by enhanced citizen loyalty as well as gaining competitive advantage, the findings of this research worth to be considered.